2018
DOI: 10.1161/strokeaha.117.019422
|View full text |Cite
|
Sign up to set email alerts
|

Association of Progression of Carotid Artery Wall Volume and Recurrent Transient Ischemic Attack or Stroke

Abstract: The annual progression of carotid wall volume is independently associated with recurrent ischemic cerebrovascular events, and this measurement has added value for intraplaque hemorrhage and fibrous cap rupture in predicting future events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…These findings confirm that IPH volume is higher in plaques causing cerebrovascular events. 2,3,5,6,31,32 Of interest, there was no difference in lipid-IPH volume tissue, whereas the total lipid volume showed a statistically significant difference. This finding can be explained because in the old classification the lipid volume class included all the voxels <60 HU (and therefore also the IPH component); these results suggest that tissues with an attenuation between 26 to 59 HU, namely fatty components, are not associated with the presence of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These findings confirm that IPH volume is higher in plaques causing cerebrovascular events. 2,3,5,6,31,32 Of interest, there was no difference in lipid-IPH volume tissue, whereas the total lipid volume showed a statistically significant difference. This finding can be explained because in the old classification the lipid volume class included all the voxels <60 HU (and therefore also the IPH component); these results suggest that tissues with an attenuation between 26 to 59 HU, namely fatty components, are not associated with the presence of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 82%
“…ABBREVIATIONS: AUC ¼ area under the curve; IPH ¼ intraplaque hemorrhage; ROC ¼ receiver operating characteristic S everal studies have demonstrated, in recent years, that the degree of stenosis should not be considered the only parameter to identify carotid plaque at risk of distal embolization and that additional plaque features can increase or reduce risk of plaque rupture and embolic events. [1][2][3][4] In particular, intraplaque hemorrhage (IPH) has been convincingly associated with a higher risk of ipsilateral cerebrovascular events. 5,6 Although MR imaging has been widely used to identify IPH, [7][8][9] recent evidence suggests that CT, 10 using a threshold of attenuation values of <25 HU in the carotid artery, can consistently identify the presence of IPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plaque volume seems to be a promising parameter related to the risk of recurrent TIA or stroke. In 2018 Lu et al 62 demonstrated that the annual progression of carotid plaque volume is independently associated with recurrent ischemic cerebrovascular events, and this measurement added value to the presence of IPH and FC rupture in terms of predicting future events. Atherosclerotic plaque volume progression and composition can facilitate the rupture of the plaques.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, high-resolution black-blood (BB) cardiovascular magnetic resonance (CMR) imaging can noninvasively visualize and quantify the vessel lumen and wall at a relatively low cost and without radiation exposure [12][13][14][15][16]. Hence, many groups have incorporated BB CMR in order to facilitate the diagnosis of carotid artery disease [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%